Budaya Pesantren sebagai Penjaga Moral Bangsa: Studi Kasus di PP. Al-Mubtadi’ien Bahrul Ulum - Mutammimah, Nisa Candra; Sofiyah Sofiyah; Agus Suprayogi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The Islamic boarding school culture at Al-Mubtadi-ien Bahrul Ulum Islamic Boarding School has proven effective in maintaining and shaping the moral values of the community through consistently implemented traditional practices. The results of qualitative research indicate that the implementation of congregational prayer, sorogan, talaman, and ta‘ziran contributes significantly to the formation of discipline, social solidarity, and moral character among students. These practices represent the integration of spiritual, intellectual, and social education in response to the phenomenon of moral degradation in modern society. The point-based ta‘ziran system has empirically been shown to reduce the level of violations and increase students’ sense of responsibility. The findings of this study complement studies in Islamic education by presenting an empirical analysis of the ability of Islamic boarding schools to adapt to the challenges of globalization. Furthermore, this Islamic boarding school education model enriches the philosophical perspective of character education based on virtue ethics and Islamic values. Therefore, Islamic boarding school administrators are advised to strengthen the integration between tradition and modernity to maintain the relevance of Islamic boarding school institutions in the future. The results of this study also have the potential to serve as a reference in the formulation of national education policies oriented toward the preservation of cultural values.